(untitled) (Revue D’études Interculturelles De L’image, 2013)
Seldom has someone emerged so unexpectedly and sensationally on to the American political scene as Sarah Palin. With Palin came what had rarely, if ever, been seen before on a presidential trail: hockey moms, Caribou-hunting, pitbulls in lipstick parcelled as political weaponry. And let’s not forget those five children, including Track 19, set to deploy to Iraq, Bristol, and her unplanned pregnancy at 17, and Trig, a six-month-old infant with Down’s syndrome. Never before had motherhood been so finely balanced with US presidential politics. Biological vigour translated into political energy, motherhood transformed into an intoxicating political ideal. This article focuses on Sarah Palin and how her brand of “rugged Alaskan motherhood” (PunditMom 2008) became central to her media image, as well as what this representation has to tell us about the relationship between mothering as a political ideal, US politics, and the media.